The effectiveness of school leadership on teachers’ performance and student achievement in Palestine - Abuaqel, Abdullah Hussein M. (2015)
Effective and successful leadership is always considered the corner-stone in the teaching and learning process. It plays a vital and tremendous role in the process. The Principal and his administrative team took the whole responsibility to enhance student learning inside and outside of classrooms. There is no doubt that they have an effective influence as they represent the role model and the superior example to be followed. The pedagogical aim of this research is to explore the relationship between schools’ Principals and Teachers, and its effect on student achievement. The variation between perceptions and practices and how this relationship can impact teaching and learning process. There are several factors , theories and concepts that play an effective role in this field. This research has focused on the Teachers’ and Principals’ practices and how they affect student achievement. A mixed methodological approach was chosen , Both qualitative and quantitative methods of research were used in this research to reach the final conclusions and resulting recommendations. Rather than using a single-method approach, which would limit the findings and data sources, the dual-method approach gives a much more holistic view of the many issues directly related to the relationship between schools’ Principals and Teachers, and its effect on student achievement. The collected data and the analysis provided by the researcher present clear evidence that leaders and teachers input has a tremendous impact on students’ academic achievement and the overall school environment as well. The results also showed that principals in the target area apply practices that are helpful to students’ achievement and this was proven through the high degree of satisfaction in the teachers reflectionand responses to the relevant items in the questionnaire. The research asserts that the principals' performance and its effect on teachers is directly proportional to the school performance and the results proved this conclusion.